Development Of Guideline On Smart Industrial Estate Management For Sustainable Growth (Journal of Namibian Studies : History Politics Culture, 2023)
Today regional and global environment is rapidly changed and expanded. The government sector realizes the importance and necessity of development of public utility, public assistance, and other facilities for entrepreneurs to support and promote the industrial advancement and service sector to meet sustainable growth as well as the supervision of environment and safety in industrial estates for economic growth, business balance, and global economic connection. The purpose of this research was to study Development of Guideline on Smart Industrial Estate Management for Sustainable Growth. Qualitative research by in depth interview from 9 experts and focus group with 11 successful businesspersons for approve this model. The sample group was 500 executives in the fields of business and industry. The research instrument used to collect data was a questionnaire. The data was analyzed by descriptive, inferential statistics, and multiple regressions.The results of the study found that the components of Development of Guideline on Smart Industrial Estate Management for Sustainable Growth were placed according to the order of their importance as follows: 1) Smart Eco System with X ̅= 4.21: the most important point was the support of utilizing solar energy generated by solar cells by providing a reasonable discount and expanding a period of factory rent to the business operators who participate the project. 2) Smart Facility.with X ̅= 4. 20 : the most important point was the implement of clean energy ortransformation of transportation ways that may reduce energy, such as pipeline transportation, rail transport, corridor lighting system, with solar energy, and so on. 3) Smart Servitization with X ̅= 4.19: the most important point was the provision of services as the Great Service Total Solution Center (TSC) do by implementing modern technology for service integration and management to meet clients or customers’ needs precisely, rapidly, and effectively. 4) Smart Regulations X ̅= 4. 15: the most important point was to monitor and follow the improvement of the law, regulations, and rules to communicate with organizations located in the industrial estates precisely,rapidly, and on time. The results of hypothesis test found that the First S-Curve and New S-Curve industries focused on the components of guidelines for smart industrial estate management to meet sustainable growth at the statistical significance level of 0.05.The results of structural equation modeling analysis found that all the indexes passed the criteria with consistency and harmony of the model and empirical data. The Chi-square minimum probability (CMIN/P) was of 0. 093, the Chi- square minimum discrepancy per degree of freedom ( CMIN/ DF) was of 1. 127, the goodness of fit index ( GFI) was of 0. 958, and the root mean square error of approximation (RMSEA) was of 0.016